Constructability implementation among Malaysian building contractors - Saghatforoush, Ehsan; Hassim, Salihudin; Jaafar, Mohd Saleh; Abdul Kadir, Mohd Razali (EuroJournals Publishing, 2009)
The basic researches about constructability issue done in different countries demonstrate the potential power of this concept to affect the total goals of the construction projects which can lead to significant cost saving, time saving and better quality via considering the contractors’ construction experience in earlier construction project phases. The present research assesses the familiarity of Malaysian building contractors with constructability concept and activities; then it tests their general opinions on its implementation in different construction phases and projects. As the result, some descriptive studies are done on amount of contractors’ familiarity with this term among various kinds of contractors, projects and contracts which can illustrate constructability implementation level among Malaysian contractors. The results of this study show that Malaysian contractors are not all familiar enough with this term and there are still some barriers that prevent them from taking part in its activities completely. The differences in amount of familiarity with constructability matter and its terms of implementation are quite obvious among various types of participants.